What is Political about Consumption? - Romanova, Regina (Journal of Economic Sociology, 2018)
This article explores the discussion about political consumerism in modern society and more broad approach to the politics of consumption in historical perspective. After the cultural turn in consumption studies the development of new analytical framework - political consumerism—is productive step for deeper understanding consumption and notion of the consumer. In particular, this paper reviews reasons for the emergence of economic understanding of consumption and how this economic understanding has led to opposition between politics and consumption. Theory of political consumerism softened the antagonistic relations between passive and self-interested consumer and active citizen, caring for the social prosperity. According to this approach, consumption is a new creative form of political participation during the societal shift to more post-materialist values and the demands for more individual autonomy. Consumers use market as an alternative sphere of political action, where their buying power is a way of restoring social justice without government. However this article argues that theory of political consumerism is linear and narrow framework for analyzing variety of the politics of consumption. Politics of consumption reflects the dynamics of the relationship between state and citizens. The notion of the consumer is shaped not only by the market economy, but also by the directive powers and interest of the state. Based on historical evidence from different countries, this paper shows the proliferation of genealogies of consumerist policy and the understandings the role of the consumer representing norms of citizenship.